Research degrees in Information and Communication Technology (ICT): Why so few doctoral students?. Issue 5 (3rd September 2017) - Guerin, Cally; Jayatilaka, Asangi; Ranasinghe, Damith; McCulloch, Alistair; Calder, Paul
Abstract: A 'knowledge society' relies on a workforce with high-level skills in Information and Communication Technology (ICT). Continuing development of ICT will arise partly from research undertaken by doctoral graduates. However, compared to other cognate disciplines, ICT has relatively few students taking up doctoral studies. This article explores some of the perceived barriers to undertaking doctoral studies in ICT in three Australian universities. Current students were surveyed regarding their post-course intentions relating to employment and further study, and the resulting data was analysed in terms of type of university attended, gender, nationality and first-in-family status. Overall, the perceived barriers to doing a research degree were related to the financial implications of such study and a limited understanding of what research in ICT involves. The following recommendations are made to universities and higher education policy-makers: that universities ensure that students have accurate information about the financial costs of doctoral studies; that students be provided with authentic undergraduate research experiences; and that pathways be developed to facilitate a smooth return to research degrees after periods of working in industry.